Incidence of shoulder and neck pain in a working population: effect modification between mechanical and psychosocial exposures at work? Results from a one year follow up of the Malmö shoulder and neck study cohort. Issue 9 (12th August 2005) - Östergren, Per-Olof; Hanson, Bertil S; Balogh, Istvan; Ektor-Andersen, John; Isacsson, Agneta; Örbaek, Palle; Winkel, Jörgen; Isacsson, Sven-Olof
Abstract : Study objective: To assess the impact of mechanical exposure and work related psychosocial factors on shoulder and neck pain. Design: A prospective cohort study. Participants: 4919 randomly chosen, vocationally active men and women ages 45–65 residing in a Swedish city. Neck and shoulder pain were determined by the standardised Nordic questionnaire. Mechanical exposure was assessed by an index based on 11 items designed and evaluated for shoulder and neck disorders. Work related psychosocial factors were measured by the Karasek and Theorell demand-control instrument. Main results: High mechanical exposure was associated with heightened risk for shoulder and neck pain among men and women during follow up. Age adjusted odds ratios (OR) were 2.17 (95% confidence intervals (CI): 1.65, 2.85) and 1.59 (95% CI: 1.22, 2.06), respectively. In women, job strain (high psychological job demands and low job decision latitude) correlated with heightened risk (OR = 1.73, 95% CI: 1.29, 2.31). These risk estimates remained statistically significant when controlled for high mechanical exposure regarding job strain (and vice versa), and for sociodemographic factors. Testing for effect modification between high mechanical exposure and job strain showed them acting synergistically only in women. Conclusion: Job related mechanical exposure in both sexes, and psychosocial factors in women, seem independently of each other to play a part for development of shoulder and neck pain in vocationally active people. The effect of psychosocial factors was more prominent in women, which could be the result of biological factors as well as gender issues. These results suggest that interventions aiming at reducing the occurrence of shoulder and neck pain should include both mechanical and psychosocial factors.